Analisis Faktor-faktor Penyebab Nasabah Debitur Melakukan Kedit Macet pada Koperasi Simpan Pinjam Pegawai Negeri MAN 2 Model Medan - Faadila Reva Alfazira; Ripho Delzy Perkasa (STKIP PGRI SITUBONDO, 2023)
This study aims to determine the factors that cause debtor customers to engage in bad credit at the Employee Savings and Loans Cooperative of MAN 2 Model Medan. The method used in this research is descriptive qualitative, namely reference sources are taken from primary and secondary data, through interviews, documentation, and from several reference sources. The results of the study show that the factors that cause debtor customers to do bad credit are; honorary teachers who do not have a fixed salary and are in a poor financial condition, then the character of the debtor's customers is also the cause of the debtor's bad credit.